Effect of several insecticide against oil palm pollinator’s weevil, Elaeidobius kamerunicus (coleoptera: curculionidae) - Yusdayati R.,; N. H. Hamid, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
Study on the effect of pesticide application against Elaeidobius kamerunicus population was carried out in lab scale. The study was divided into two parts which are the direct effect against the weevil and indirect effect against the eggs. Cypermethrin showed the highest toxicity level compared to the other types of pesticides as the application eliminate all weevil population after one day of application (DAA). The mortality rate of weevil was significantly different only on the first day after application (F= 268.86, p<0.05). Result of our field study indicate that there were significant different in the number of weevil resurgence between the pesticide application and control (F= 93.75 p<0.05) except for Bacillus thuringiensis. The application of cypermethrin, chlorantraniliprole and Bacillus thuringiensis had a negative effect on the weevil directly. Meanwhile, the application of B. thuringiensis did not affect the eggs of E. kamerunicus.